Renewable Energy Auction Prices: Near Subsidy-Free? - Helena Martín; Sergio Coronas; Àlex Alonso; Jordi de la Hoz; José Matas (Energies, 2020)
The latest trend of low record bid prices in renewable energy auctions has raised concerns on the effective deployment of the winning projects. A survey of recent auction data from several countries, technologies and remuneration designs is analysed and compared with the corresponding levelised costs of energy (LCOEs) to draw first insights on their viability. A critical assessment of the ability of the LCOE for determining the adequate bid level is then performed and the preliminary unviable results of selected mature technologies are further investigated using improved profitability metrics as the project and equity net present value (NPV) and internal rate of return (IRR). As representative examples, the analysed Danish 2019 onshore wind and photovoltaics (PV) auctions require very specific scenarios to become viable, which cast doubts on their effective implementation. Under the assumptions of a realistic base case, the sensitivity analysis revealed that either 59% of decrease in the weighted average cost of capital (WACC), or 37% of discount on the investment cost or a 3.6% annual increment in the mean market price is needed for achieving the NPV break-even in the onshore wind case. Likewise, the PV case is unprofitable whatever the WACC may be, and either a 60% discount on the investment cost or a 6.8% annual increment in the mean market price is needed for the NPV to break-even. Although some projects could be relying on indirect revenues or additional sources of incomes beyond the auction support, it remains to see if they are finally materialised.